Investigators' Experience With Expedited Safety Reports Prior to the FDA's Final IND Safety Reporting Rule. (July 2014) - Kramer, Judith M.; Vock, David; Greenberg, Howard E.; Janning, Cheri; Szczech, Lynda; Salgo, Miklos; Gagnon, Suzanne; Ellenberg, Susan
Prior to enactment of the final investigational new drug application (IND) safety reporting rule, an attempt was made to document the effort expended at investigative sites in processing IND safety reports from sponsors and to assess the effect of these expedited reports on trial conduct. Investigators were asked to (1) prospectively document time to process IND safety reports and (2) retrospectively review safety reports from a previous 3-month period, documenting resultant actions. In this limited sample, sites spent a median of 0.25 hours per report at a median cost of US22. Few expedited safety reports were retrospectively said to have changed study conduct or informed consent. However, a low response rate and the concentration of clinical sites in a single therapeutic area preclude generalizing these results. The authors discuss the challenges in gaining investigators' cooperation to evaluate the impact of regulatory requirements. Better methods to facilitate this type of research will enrich the scientific basis of future clinical trial regulation and guidance.